Magnetic resonance spectroscopic evidence of increased choline in the dorsolateral prefrontal and visual cortices in recent onset schizophrenia. (23rd January 2022) - Smucny, Jason; Carter, Cameron S.; Maddock, Richard J.
Highlights: Dorsolateral prefrontal cortex dysfunction is evident in recent onset schizophrenia. Elevated choline-containing metabolites were observed in DLPFC in such patients. Similar elevation of the 1H-MRS choline signal was observed in the visual cortex. Increased choline may reflect membrane remodeling associated with neuroinflammation. Abstract: A complete characterization of neurometabolite profiles in the dorsolateral prefrontal cortex (DLPFC) in recent onset schizophrenia (SZ) remains elusive. Filling in this knowledge gap is essential in order to better understand how the neurochemistry of this region contributes to SZ pathology. To that end, DLPFC N-acetyl aspartate (NAA), myo-inositol, glutamate, choline, and creatine levels were examined by 3 T magnetic resonance spectroscopy (MRS) in recent onset individuals with SZ ( n  = 40) and healthy controls (HC) ( n  = 47). Metabolite levels were also examined in the visual cortex (VC) as a control region. People with SZ showed significantly higher choline in both the DLPFC and VC, but no differences in NAA, myo-inositol, glutamate, or creatine in either region. A trend-level negative correlation was also observed between DLPFC NAA and negative symptoms in SZ. Our results suggest that choline is increased in both the prefrontal and occipital cortices in recent onset SZ, and that DLPFC NAA levels may be inversely related to negative symptoms in the illness. The observed increase in choline-containing compounds in both DLPFC and VC in recent onset SZ could reflect increased membrane remodeling such as occurs in activated microglia and astrocytes in response to neuroinflammation.